What Drives Brand Equity? The Perspective of Malaysian Consumers - Mohd Yasin, Norjaya; Noor, Mohd Nasser; Mohamad, Osman (Universiti Utara Malaysia Press, 2006)
Considering the importance of brand equity in brand management and the role played by brand equity in the success of the firm, this study examines the factors that influence the formation of brand equity particularly the equity of brands of household electrical appliances namely televisions, refrigerators and air-conditioners. In the conceptual model of brand equity, the dimensions of brand awareness, brand loyalty, perceived quality, and brand associations are postulated to affect the formation of brand equity. On the basis of an analysis of a survey data of 501 respondents taken from consumers of household electrical appliances in the state of Selangor and the Federal Territory of Kuala Lumpur; this study found that the dimensions of brand equity comprised of three elements, namely, brand distinctiveness, brand loyalty, and brand awareness/associations. These three elements were found to have positive and significant influences on the formation of brand equity of electrical goods.